Languages about Languages: Two Brothers and one Humboldtian Science - Ette, Ottmar (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2018)
Abstract In the history of Humboldt research both brothers have been traditionally seen as representing the dichotomy between the humanities and the natural sciences. Today however, their similar approach to using and forming scientific language could be used as a starting point for conceiving a university, museum and even forum under one single Humboldtian science. Zusammenfassung In der Vergangenheit sah die Humboldt-Forschung beide Brüder als Vertreter gegenteiliger wissenschaftlicher Ansätze. Heute jedoch kann ihr ähnlicher Zugang zu wissenschaftlicher Sprache als Ausgangspunkt für die Konzipierung einer Universität, eines Museums und Forums unter einer einzigen Humboldtschen Wissenschaft genutzt werden. Resumen En la investigación humboldtiana, los hermanos tradicionalmente representaban la oposición entre las humanidades y las ciencias naturales. Hoy, en cambio, su enfoque similar de usar y construir las lenguas y los discursos de sus respectivas disciplinas se puede usar como punto de partida en concebir una universidad, un museo y un fórum desde una sola ciencia humboldtiana. Lecture held on the occasion of Leibniz Day, 2017 of the Berlin-Brandenburg Academy of Sciences and Humanities